2016
DOI: 10.1002/j.0022-0337.2016.80.9.tb06193.x
|View full text |Cite
|
Sign up to set email alerts
|

A Training Program Using an Audience Response System to Calibrate Dental Faculty Members Assessing Student Clinical Competence

Abstract: The aim of this study was to assess the effectiveness of calibration training of departmental faculty and competency graders using an audience response system on operative dentistry concepts across 12 months. The training sessions were designed to further solidify the process and equilibration of clinical opinions among faculty members and provide a more calibrated grading assessment during patient care for student performance feedback. Four (quarterly) calibration sessions occurred over 12 months in 2015. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
4
Order By: Relevance
“…Moreover, the personalities of clinical instructors are different from each other, and clinical instructor's different characteristics also affects clinical teaching effectiveness [11,12].Therefore, although there are personalized, group-style lectures in clinical training process, it is difficult to achieve complete standardized, unified clinical training effectiveness. It had revealed that the lack of standardization occurs, resulting in discrepancies among training effectiveness [13]. Thus, the unity of clinical training process is important in dental clinical education [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the personalities of clinical instructors are different from each other, and clinical instructor's different characteristics also affects clinical teaching effectiveness [11,12].Therefore, although there are personalized, group-style lectures in clinical training process, it is difficult to achieve complete standardized, unified clinical training effectiveness. It had revealed that the lack of standardization occurs, resulting in discrepancies among training effectiveness [13]. Thus, the unity of clinical training process is important in dental clinical education [14].…”
Section: Discussionmentioning
confidence: 99%
“…Standardized rubrics are also likely to minimize problems with faculty calibration 10 . In an ideal setting, all clinical instructors would have participated in preclinical courses, which is perhaps the most efficient method of faculty calibration 11 . The reality, however, is that not all clinical faculty members have the opportunity to participate in preclinical courses.…”
Section: Discussionmentioning
confidence: 99%
“…When clinical instructors are not assigned to preclinical courses, a lack of standardization occurs, resulting in discrepancies among instructors. Discrepancies can exist in terminology, preparation design, and restoration design 11 . Faculty calibration is an essential process to allow more consistent evaluation with meaningful feedback to students’ performance both preclinically and clinically.…”
mentioning
confidence: 99%
“…43 Fakültede kalibrasyon olmayışı; klinik derslerde mevcut olan ilave ve sık karşılaşılan bir sorundur. 44…”
Section: öğRencilerin Klinik Ortamında öğRenme Ve Değerlendirilmeleriunclassified
“…İdeal olarak öğrencinin öğrenim seviyesi yükselirken, klinik eğitmenin kalibrasyon kazanmasına fırsat vermesi için, eğitmenin öğrencileri klinik ortamda değerlendirmeden önce preklinik derslerde görev alması gerekir. Klinik eğitmenler preklinik derslerde görev almayınca, standardizasyon yapılamaz ve eğitmenler arasında terminoloji, preparasyon ve restorasyon tasarımları açısından farklılıklar oluşur 44. Fakülte kalibrasyonu; öğrencilerin klinik ve preklinik performanslarında anlamlı geri bildirim oluşturarak, daha tutarlı değerlendirmeye imkan sağlar.Günlük klinik puanlamalar ve puanla değerledirmeler mukayese edildiğinde de çelişkiler ortaya çıkmaktadır.…”
unclassified